The associations of poor psychiatric well-being among incarcerated men with injecting drug use histories in Victoria, Australia - Reece Cossar; Mark Stoové; Stuart A. Kinner; Paul Dietze; Campbell Aitken; Michael Curtis; Amy Kirwan; James R. P. Ogloff (BMC, 2018)
Abstract Background Dual substance dependence and psychiatric and psychological morbidities are overrepresented in prison populations and associated with reoffending. In the context of an increasing prison population in Australia, investigating the needs of vulnerable people in prison with a dual diagnosis can help inform in-prison screening and treatment and improve prison and community service integration and continuation of care. In this study we quantified psychiatric well-being in a sample of people in prison with a history of injecting drug use in Victoria, Australia, and identified factors associated with this outcome. Methods and Results Data for this paper come from baseline interviews undertaken in the weeks prior to release as part of a prospective cohort study of incarcerated men who reported regular injecting drug use prior to their current sentence. Eligible participants completed a researcher-administered structured questionnaire that canvassed a range of issues. Psychiatric well-being was assessed using the 12-item General Health Questionnaire (GHQ-12) and potential correlates were included based on a review of the literature. Of the 317 men included for analyses, 139 were classified as experiencing current poor psychiatric well-being. In the multivariate model using modified logistic regression, history of suicide attempt (aOR = 1.36, 95%CI 1.03-1.78), two or more medical conditions (aOR = 1.87, 95%CI 1.30-2.67) and use of crystal methamphetamine in the week prior to their current sentence (aOR = 1.52, 95%CI 1.05-2.22) were statistically significantly associated with current poor psychiatric well-being. Conclusions Comprehensively addressing the health-related needs for this vulnerable population will require a multidisciplinary approach and enhancing opportunities to screen and triage people in prison for mental health and other potential co-occurring health issues will provide opportunities to better address individual health needs and reoffending risk.